2012
DOI: 10.1007/s00011-012-0540-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and non-infectious factors in the aetiology of pharyngitis (sore throat)

Abstract: ObjectivesThe aim of this review is to examine the causes, pathophysiology and experimental models of noninfectious pharyngitis (sore throat). Introduction The causes of sore throat can be infectious (viruses, bacteria, and fungi) or non-infectious, although the relative proportion of each is not well documented. Methods A PubMed database search was performed for studies of non-infectious sore throat. Results and conclusions Non-infectious causes of sore throat include: physico-chemical factors, such as smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 139 publications
(162 reference statements)
4
55
0
12
Order By: Relevance
“…[1][2][3] Inflammatory mediators are thought to be responsible for sore throat, as demonstrated in studies where nasal or oropharyngeal challenge with bradykinin and prostaglandins caused sore throat symptoms, [3][4][5][6] and stimulation of the pharyngeal mucosa with cold dry air increased inflammatory mediators and caused pain. [7] Most adult cases ($85-95%) are caused by viral upper respiratory tract infection (URTI), [1,2] although other causes include bacterial infections (including group A bhaemolytic streptococcus [GABHS], $10% of cases) and non-infectious factors including smoking and air pollution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Inflammatory mediators are thought to be responsible for sore throat, as demonstrated in studies where nasal or oropharyngeal challenge with bradykinin and prostaglandins caused sore throat symptoms, [3][4][5][6] and stimulation of the pharyngeal mucosa with cold dry air increased inflammatory mediators and caused pain. [7] Most adult cases ($85-95%) are caused by viral upper respiratory tract infection (URTI), [1,2] although other causes include bacterial infections (including group A bhaemolytic streptococcus [GABHS], $10% of cases) and non-infectious factors including smoking and air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Most adult cases ($85-95%) are caused by viral upper respiratory tract infection (URTI), [1,2] although other causes include bacterial infections (including group A bhaemolytic streptococcus [GABHS], $10% of cases) and non-infectious factors including smoking and air pollution. [2,3] URTI is a common reason for primary care consultations and as viruses cause most sore throats, antibiotics are not usually appropriate. [1,8] However, physicians continue to prescribe antibiotics inappropriately for sore throat and these prescribing practices contribute to the growing global problem of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also reported a higher prevalence of acute pharyngitis compared to chronic or recurrent. 10,11 None of the subjects had history of allergic reactions to the commonly used AMAs like beta-lactams, flouroquinolones or macrolides. Recording and scrutinizing the data about the previous medications may help to analyse the pattern of exposure to AMAs, to elicit any history of allergy or intolerance and also to consider any possibility of resistance to the previous AMA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Sore throat or pharyngitis is very common, largely seasonal conditions that are primarily caused by a viral infection of the upper respiratory tract (URT) [1][2][3]. While rhinoviruses, responsible for the common cough and cold, do not afflict significant damage to the respiratory mucosa, Influenza A infection can be much more serious [4].…”
Section: Introductionmentioning
confidence: 99%